THE IMPACT OF STRESS ON ACADEMIC ACHIEVEMENT - Lawal, Suleiman (Sokoto Educational Review, 2020)
This paper examined the impact of stress on academic achievement. Stress has become a common health problem. Several recent illnesses have been attributed to stress. The writer defined the concept stress, gave it sources and highlighted on the major symptoms of stress. The writer went on to highlight the real impact of stress on academic' achievement, where the discussed about, how stress bring about poor study habit, lack of concentration, poor memory, fear of test/examination and hate for the study. Strategies and techniques of managing stress were also discussed. Lastly conclusion and recommendations were drawn by the writer.